The Effectivity of Shalat on Cognitive Function in the Elderly - Boy, Elman; Hasanah, Nur; Freeman, Cindy Azzahra; Furqoni, Aminullah (Universitas Muhammadiyah Semarang, 2022)
Background: When humans enter the old phase, humans will experience physical, mental, social, and health changes and many older people feel alone, frustrated, and finally lose confidence in their health. One of the efforts to improve the health of the elderly can be made by increasing physical activity such as prayer.Objective: Our study aims to review the effect of Islamic prayer (shalat) on the cognitive function of moslems aged 60 and over.Method: Journal searches are conducted with English studies relevant to the topic and are carried out using ProQuest, SagePub, PubMed, Google Scholar, and Semantics databases. The journal year used is limited from 2015 to 2020. The related journals used in this research are four journals.Results: The study results reported that about 95% of the elderly said that praying five times a day would help their cognitive function healthy. These similarities suggest that exercise can help older adults maintain their cognitive abilities, whether prayer or exercise only. Prayer as physical activity may be beneficial for general and selective cognitive aspects, especially among older adults.Conclusion: prayer is an activity that can be done by the elderly and has several sound effects on cognitive function.